2017
DOI: 10.1097/tp.0000000000001405
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit in Older Patients Associated With Earlier Transplant With High KDPI Kidneys

Abstract: Background Given high dialysis mortality rates for patients >60 years old, accepting a kidney with a high kidney donor profile index (KDPI) score could enable earlier and potentially preemptive transplantation (preKT). However, evidence regarding the risks of high KDPI allografts in older patients is limited. Our objective was to determine the relative benefit for older patients of KDPI>85% transplant either preemptively or not compared with remaining on the waitlist. Methods UNOS data from 2003–2012 for adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 22 publications
3
101
0
2
Order By: Relevance
“…Currently, >60% of such grafts with a high KDPI (>85%) are discarded, representing approximately 3000 kidneys annually in the USA . Transplantation of grafts with a KDPI >85% was reported to be an acceptable option for older patients compared with remaining on the waiting list . In Japan, the number of deceased‐donor renal transplantations is extremely small .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, >60% of such grafts with a high KDPI (>85%) are discarded, representing approximately 3000 kidneys annually in the USA . Transplantation of grafts with a KDPI >85% was reported to be an acceptable option for older patients compared with remaining on the waiting list . In Japan, the number of deceased‐donor renal transplantations is extremely small .…”
Section: Discussionmentioning
confidence: 99%
“…24 Transplantation of grafts with a KDPI >85% was reported to be an acceptable option for older patients compared with remaining on the waiting list. 25 In Japan, the number of deceased-donor renal transplantations is extremely small. 26 Determining the best way to increase the number of deceased-donor renal allografts and maintaining the vitality of renal allografts recovered from DCD donors thus remains an important issue for renal transplant surgeons in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Furthermore, multiple studies have documented the survival benefit associated with high KDPI transplant compared with waitlist mortality including those who go on to undergo low KDPI transplant. [24, 25] Interestingly, donor acceptance patterns are also undoubtedly highly influenced by fiscal realities. Schold et al demonstrated even greater reductions in living donor kidney transplants (LDKT) compared with ECD transplants in centers with LP evaluations as highlighted in Figure 2.…”
Section: Unitended Consequences and Disincentivesmentioning
confidence: 99%
“…Additionally, two recent observational studies have shown that utilization of kidneys with a high Kidney Donor Profile Index (>85%) or deceased diabetic donor kidneys also provides a higher survival in older recipients compared with waitlisted patients [64, 65]. However, an elegant Dutch observational study performed in elderly KT patients receiving deceased-donor grafts from elderly donors (≥65 years) demonstrated an increased mortality risk compared with waitlisted elderly patients remaining on dialysis [66].…”
Section: Comparing Mortality Risk On Waiting-list Versus Post-transplmentioning
confidence: 99%